Evaluation of the low temperature and elastic properties of crumb rubber and SBS modified bitumen and mixtures - Kök, Baha Vural; Yılmaz, Mehmet; Geçkil, Alaaddin (My University, 2013)
Abstract: In this study, the performances of bitumen and asphalt mixtures modified by crumb rubber (CR) were compared with those modified by styrene-butadiene-styrene (SBS). The resultant mixtures were evaluated for their rheological and mechanical performances by different experimental techniques such as rheological bitumen tests, i.e., dynamic shear rheometer (DSR), bending beam rheometer (BBR), and hot mixture performance tests, that is, indirect tensile stiffness modulus, fatigue, semicircular bending, and toughness index. Experimental studies show that it is necessary to use twice as much CR as SBS to reach the same performance attained by SBS. CR modification at high additive content exhibits higher elastic response, i.e., recoverable strain, than the SBS-modified mixture. While the resistance to crack initiation of CR-modified mixtures increases with increasing additive content, the resistance to crack propagation decreases dramatically according to fatigue and semicircular bending tests.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Crumb rubber; Styrene-butadiene-styrene; Rheological properties; Performance tests; Crack prppagation